Factors associated with cognitive impairment and cognitive concerns in patients with metastatic non-small cell lung cancer. Issue 1 (7th September 2021) - Eggen, Annemarie C; Richard, Nadine M; Bosma, Ingeborg; Jalving, Mathilde; Leighl, Natasha B; Liu, Geoffrey; Mah, Kenneth; Higazy, Randa; Shultz, David B; Reyners, Anna K L; Rodin, Gary; Edelstein, Kim
Abstract: Background: Knowledge regarding cognitive problems in metastatic non-small cell lung cancer (mNSCLC) is limited. Such problems may include both patient-reported cognitive concerns and demonstrable cognitive impairment. Greater understanding of these outcomes is needed to inform rehabilitation strategies for these difficulties. We aimed to identify the frequency of cognitive problems and associated factors in patients with mNSCLC. Methods: In this cross-sectional study, adults with mNSCLC completed validated neuropsychological tests and self-report questionnaires measuring cognitive concerns, neurobehavioral concerns, depression, demoralization, illness intrusiveness, self-esteem, and physical symptoms. Cognitive impairment (performance based) was defined according to International Cancer and Cognition Task Force criteria. Clinically significant cognitive concerns were defined by a score ≥1.5 SD below the normative mean on the Functional Assessment of Cancer Therapy-Cognitive Function Perceived Cognitive Impairment (FACT-Cog PCI). Univariate and multivariate logistic regression analyses were performed to identify associated factors. Results: Of 238 patients approached, 77 participated (median age: 62 years; range: 37-82). Brain metastases were present in 41 patients (53%), and 23 (29%) received cranial irradiation. Cognitive impairment and cognitive concerns were present in 31 (40%) and 20 patients (26%), respectively. Cognitive impairment and cognitive concerns co-occurred in 10 patients (13%), but their severity was unrelated. Cognitive impairment was associated with cranial irradiation (odds ratio [OR] = 2.89; P = .04), whereas cognitive concerns were associated with greater illness intrusiveness (OR = 1.04; P = .03) and lower self-esteem (OR = 0.86; P = .03). Conclusions: Cognitive impairment and cognitive concerns are both common in patients with mNSCLC but are not necessarily related, and their risk factors differ. The association of illness intrusiveness and self-esteem with cognitive concerns can inform therapeutic interventions in this population.